Effect of electric field configuration on streamer and partial discharge phenomena in a hydrocarbon insulating liquid under AC stress. (6th April 2016) - Liu, Z; Liu, Q; Wang, Z D
Abstract: This paper concerns pre-breakdown phenomena, including streamer characteristics from a fundamental perspective and partial discharge (PD) measurements from an industrial perspective, in a hydrocarbon insulating liquid. The aim was to investigate the possible changes of the liquid's streamer and PD characteristics and their correlations when the uniformity of the AC electric field varies. In the experiments, a plane-to-plane electrode system incorporating a needle protrusion was used in addition to a needle-to-plane electrode system. When the applied electric field became more uniform, fewer radial branches occurred and streamer propagation towards the ground electrode was enhanced. The transition from streamer propagation dominated breakdown in divergent fields to streamer initiation dominated breakdown in uniform fields was evidenced. Relationships between streamer and PD characteristics were established, which were found to be electric field dependent. PD of the same apparent charge would indicate longer streamers if the electric field is more uniform.